Investigation on the chemical effects of dimethyl ether and ethanol additions on PAH formation in laminar premixed ethylene flames. (15th November 2019) - Zhang, Yiran; Li, Youping; Liu, Peng; Zhan, Reggie; Huang, Zhen; Lin, He
Abstract: This paper presents a comparative study focusing on the chemical effects of dimethyl ether (DME) and ethanol (EtOH) on PAH formation in fuel-rich laminar premixed ethylene flames using laser-induced fluorescence (LIF) diagnostic. To investigate the chemical effects, the equivalence ratios, dilution ratios, and temperature profiles were kept nearly constant while DME and EtOH were separately blended into the ethylene-base flame. The LIF testing data showed that the PAH formation was observably suppressed by the DME and EtOH additions, and DME was much more effective at suppressing the PAH formation than EtOH. To reveal the mechanism of the inhibiting effects of oxygenated fuels on PAH formation, chemical kinetic analysis was conducted. The model results captured the variation tendency of PAHs observed in experiments and indicated that the decreased concentration of carbon which was available to form the first aromatic ring (benzene) is the main reason for PAH reduction with EtOH and DME additions. Moreover, during the growth process from benzene to PAHs, the C2 H2 -addition reactions, which played a key role in the formation of new aromatic rings, were suppressed due to less C2 H2 formed in EtOH and DME addition flames. There was less C2 H2 produced from DME than that from EtOH, therefore, DME had a stronger inhibiting effect than EtOH on PAH formation in laminar premixed ethylene flames.